Biological Activities Of Extracts From Green Marine Macroalgae, Halimeda Discoidea - Supardy, Nor Afifah (2011)
Macroalgae Halimeda discoidea was studied for its bioactivities and characterization of the bioactive fraction was carried out. The antimicrobial activity of 8 extracts with different polarities (methanol, ethyl acetate, diethyl ether, butanol, hexane and chloroform) was started with the screening against 18 bacteria, three yeast and five fungi, through the disc diffusion method. The result revealed that hexane extract was the most active extract, followed by the ethyl acetate (Soxhlet) and chloroform extracts. Hexane extract was active against five Gram-positive and three Gram-negative bacteria and two yeasts.